Pengaruh Motivasi, Kepuasan, dan Lingkungan Kerja Terhadap Kinerja Karyawan Divisi Shipping Garment PT. Danliris Sukoharjo. - Endra Wahyu Rochmadi; Istiatin; Istiqomah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Employees of the Shipping Garment Division of Sukoharjo are the focus of this study. The purpose of this study is to determine the Influence of Motiv|ation, S|atisf|action, |and Work Environment on the Perform|ance of Employees of the Shipping Garment Division of PT. Danliris Sukoharjo. Descriptive quantitative methodology is used in this study. Employees of the Shipping G|arment Division |are the popul|ation of the study, |and 72 responses |are the s|ample. The results of d|at|a |an|alysis show th|at the t-test of work motiv|ation is signific|ant (0.000 <0.05) |and re|aches t-count> t-t|able (3.211> 1.994). Job s|atisf|action is signific|ant (0.000 <0.05) |and t-count> t-t|able (2.057> 1.994). work environment is signific|ant (1.178> 0.05) |and t-count <t-t|able (1.178 <1.994). Therefore, employee perform|ance |at PT D|anliris Sukoh|arjo is significantly influenced by motivation and product satisfaction, but is not influenced by the work environment.